Add-On MEmaNtine to Dopamine Antagonism to Improve Negative Symptoms at First Psychosis- the AMEND Trial Protocol - Sandström, Katharina O.; Baltzersen, Olga B.; Marsman, Anouk; Lemvigh, Cecilie K.; Boer, Vincent O.; Bojesen, Kirsten B.; Nielsen, Mette Ø.; Lundell, Henrik; Sulaiman, Daban K.; Sørensen, Mikkel E.; Fagerlund, Birgitte; Lahti, Adrienne C.; et al. (Frontiers in Psychiatry, 2022)
Background: Antipsychotic drugs are primarily efficacious in treating positive symptoms, but fail to substantially improve negative symptoms and cognitive deficits. The limited efficacy may be attributed to the pathophysiology of psychosis which involves multiple neurotransmitter systems. In patients with chronic schizophrenia, memantine, a non-competitive glutamatergic NMDA receptor antagonist, shows promise for ameliorating negative symptoms. Yet, it is unknown how memantine modulates glutamate levels, and memantine has not been investigated in patients with first-episode psychosis. Aims: This investigator-initiated double-blinded randomized controlled trial is designed to test the clinical effects on negative symptoms of add-on memantine to antipsychotic medication, and to neurobiologically characterize responders to add-on memantine. Materials and Equipment: Antipsychotic-naïve patients with first-episode psychosis will be randomized to 12 weeks treatment with [amisulpride+memantine] or [amisulpride+placebo]. Minimum 18 patients in each treatment arm will complete the trial. Brain mapping will be performed before and after 12 weeks focusing on glutamate and neuromelanin in predefined regions. Regional glutamate levels will be probed with proton magnetic resonance spectroscopy (MRS), while neuromelanin signal will be mapped with neuromelanin-sensitive magnetic resonance imaging (MRI). Structural and diffusion weighted, whole-brain MRI will be performed. MRS and MRI will be performed at an ultra-high field strength (7 Tesla). Alongside, participants undergo clinical and neuropsychological assessments. Twenty matched healthy controls will undergo baseline- and 12-week examinations, without treatment. Outcome Measures: Primary endpoint is negative symptoms. Secondary outcomes comprise: clinical endpoints related to cognition, psychotic symptoms, side effects, and neurobiological endpoints related to regional glutamate- and neuromelanin levels, and structural brain changes. Anticipated Results: We hypothesize that add-on memantine to amisulpride will be superior to amisulpride monotherapy in reducing negative symptoms, and that this effect will correlate with thalamic glutamate levels. Moreover, we anticipate that add-on memantine will restore regional white matter integrity and improve cognitive functioning. Perspectives: By combining two licensed, off-patent drugs, AMEND aims to optimize treatment of psychosis while investigating the memantine response. Alongside, AMEND will provide neurobiological insights to effects of dual receptor modulation, which may enable future stratification of patients with first-episode psychosis before initial antipsychotic treatment. Clinical Trial Registration: EudraCT nr: 2021-001061-20, ClinicalTrials.gov (NCT04789915).